Preliminary Study on Water Bodies’ Effects on the Decomposition Rate of Goldenrod Litter - Szabina Simon (MDPI AG, 2021)
Leaf-litter input constitutes a major load in natural waters; therefore, to achieve and maintain high water quality, it is important to thoroughly examine and understand the litter decomposition process. The widespread Solidago canadensis exerts a negative effect on the composition of the ecosystem, causes extinction of species, and modifies the function of the system. In Hungary, goldenrod constantly spreads to newer areas, which can also be observed around Lake Balaton and at the bank of the Hévíz canal. In our investigation, we examined the decomposition rate of the leaves and stems of the goldenrod with the commonly applied method of leaf litter bags. As water temperature, ranging from 24.0 °C to 13.7 °C, decreases in Hévíz canal away from Lake Hévíz (−0.32 °C/100 m), we chose three different sampling sites with different water temperatures along the canal to determine how water temperature influences the rate of decomposition. For both leaves and stems, the fastest decomposition rate was observed at the first site, closest to the lake. At further sites with lower water temperatures, leaf litter decomposition rates decreased. Results observed through Hévíz canal demonstrated that higher water temperature accelerated the goldenrod decomposition dynamics, while the drift also impacted its efficiency.